The Effect of Electrolyzer Installation on 4-Stroke Modified Injection Motorcycle on Fuel Consumption and Exhaust Gas - Ridho Wahyudi; Wawan Purwanto; Hasan Maksum; M. Yasep Setiawan; Yoga Guntur Sampurno (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
The increasing population of motorbikes has an impact on fuel needs and the resulting increase in exhaust emissions. The electrolyzer has an effect on fuel consumption and gasoline exhaust of a modified 4-stroke motorbike. This research is experimental research, starting with designing and making the tools to be studied, then conducting research. As a result, there was a decrease in fuel consumption of 31.36% at 2000 RPM rotation, 8.73% at 4000 RPM engine speed, and 15.48% at 6000 RPM rotation. While exhausting emissions, there was a decrease in CO of 47.37%, an increase in h22o of 24.37%, and a decrease in HC of 45.11% at 2000 RPM rotation. The 4000 RPM rotation decreased CO by 89.11%, CO2 increased by 35.48%, and HC decreased by 36.98%. The 6000 RPM rotation decreased CO by 41.67%, CO2 increased by 17.26% and HC decreased by 6.92%. Semakin banyak populasi sepeda motor berdampak pada kebutuhan bahan bakar dan meningkatnya emisi gas buang yang dihasilkan. Elektroliser berpengaruh pada konsumsi bahan bakar dan gas buang sepeda motor 4 langkah modifikasi injeksi. Penelitian ini merupakan penelitian eksperimen, dimulai dengan merancang dan membuat alat yang akan diteliti, kemudian dilakukan penelitian. Hasilnya, terjadi penurunan konsumsi bahan bakar sebesar 31.36% pada putaran 2000 RPM, 8.73% pada putaran mesin 4000 RPM dan 15.48% pada putaran 6000 RPM. Sedangkan emisi gas buang, terjadi penurunan CO sebesar 47.37%, kenaikan CO2 sebesar 24.37% dan penurunan HC sebesar 45.11% pada putaran 2000 RPM. Putaran 4000 RPM terjadi penurunan CO sebesar 89.11%, kenaikan CO2 sebesar 35.48%, dan penurunan HC sebesar 36.98%. Putaran 6000 RPM terjadi penurunan CO sebesar 41.67%, kenaikan CO2 sebesar 17.26% dan penurunan HC sebesar 6.92%.